2019
DOI: 10.1152/ajprenal.00624.2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing novel olfactory receptors expressed in the murine renal cortex

Abstract: A primary function of the kidney is to maintain homeostasis. Recent studies have shown that specialized G‐protein coupled receptors, such as olfactory receptors (ORs), play essential roles in modulating kidney function. However, ORs are often orphan receptors with unknown ligands. In a recent RNA seq screen we identified 11 ORs as expressed in the renal cortex, including 5 ORs we had previously published as being expressed in the kidney, and 6 novel ORs. We have previously published the results of ligand scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 86 publications
2
38
0
Order By: Relevance
“…Overall, our results on activation of OR51E1 by aliphatic acids but not structurally similar compounds ( Fig. 4 ) were consistent with those earlier studies where the OR expression at the protein level was convincingly demonstrated ( 11 , 18 ). Having established the functional activity of the overexpressed OR51E1 and OR51E2, we focused on their cancer-related properties, i.e.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, our results on activation of OR51E1 by aliphatic acids but not structurally similar compounds ( Fig. 4 ) were consistent with those earlier studies where the OR expression at the protein level was convincingly demonstrated ( 11 , 18 ). Having established the functional activity of the overexpressed OR51E1 and OR51E2, we focused on their cancer-related properties, i.e.…”
Section: Resultssupporting
confidence: 93%
“…Olfr558 appears to be responsible for sensing nutrients such as butyrate and isovaleric acid in the gut ( 17 ). The human ortholog OR51E1 is also activated by butyrate and other aliphatic acids ( 18 ). Some investigators reported activation of OR51E2 by other chemicals, e.g.…”
mentioning
confidence: 99%
“…Recently, these proteins have also been shown to have important roles in other tissues as well. For example, ectopically expressed ORs have been found throughout the body including the testis ( Feldmesser et al, 2006 ; Kang and Koo, 2012 ), heart ( Feldmesser et al, 2006 ; Kang and Koo, 2012 ; Flegel et al, 2013 ), kidney ( Feldmesser et al, 2006 ; Kang and Koo, 2012 ; Pluznick and Caplan, 2012 ; Flegel et al, 2013 ; Rajkumar et al, 2014 ; Halperin Kuhns et al, 2019 ), brain ( Feldmesser et al, 2006 ; Kang and Koo, 2012 ; Flegel et al, 2013 ), thyroid ( Feldmesser et al, 2006 ; Flegel et al, 2013 ), and pancreas ( Feldmesser et al, 2006 ; Kang and Koo, 2012 ), while TRs and Opns have also been identified in the airway epithelium ( Li, 2013 ; Gilca and Dragos, 2017 ), large and small intestine ( Li, 2013 ; Gilca and Dragos, 2017 ), adrenal glands ( Halford et al, 2001 ; Li, 2013 ), and kidney ( Halford et al, 2001 ). While the physiological relevance of these receptors is continuing to emerge, many of these ‘extra sensory’ localizations have been linked to physiological and pathophysiological functions ( Spehr et al, 2003 ; Neuhaus et al, 2009 ; Sharma et al, 2017 ; Abaffy et al, 2018 ; Massberg and Hatt, 2018 ; Lee et al, 2019 ; Tole et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the tissues, in which the presence and function of ORs is investigated, is the kidney (Halperin Kuhns et al, 2019; Miyamoto et al, 2016; Peti-Peterdi, Kishore, & Pluznick, 2016; Pluznick et al, 2009; Rajkumar, Aisenberg, Acres, Protzko, & Pluznick, 2014; Shepard & Pluznick, 2017). Studies using unsupervised high-throughput techniques have discovered the existence of these receptors in the kidney (Feldmesser et al, 2006; Flegel, Manteniotis, Osthold, Hatt, & Gisselmann, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Shepard et al demonstrated that Olfr1393 participates in glucose transportation in both normal and pathological states of the kidney (Shepard et al, 2016; Shepard, Koepsell, & Pluznick, 2019). Considering the magnitude of this gene family (around 1000 genes in the mouse and 400 genes in the human) as well as their role in chemo-sensation, more investigations are needed to uncover the role of other OR subtypes in kidney function and hemostasis (Halperin Kuhns et al, 2019; Shepard & Pluznick, 2016).…”
Section: Introductionmentioning
confidence: 99%